Tirzepatide in Sport: A Comprehensive Review of its Metabolic Impacts and Potential Applications for Athletes - Wiktor Biesiada; Ewelina Kopczyńska; Piotr Kulej; Justyna Woźniak; Justyna Weronika Kmieć; Anna-Mariia Chernysh; Aleksandra Dusińska; Jakub Waszczyński; Kamila Fuczyło; Karolina Stankevič (Quality in Sport)
Introduction Tirzepatide, a dual agonist of glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide-1 (GLP-1) receptors, has emerged as a transformative metabolic therapy with exceptional efficacy in weight management and glycemic control. Its relevance in sports science is growing, with potential benefits in weight optimization, energy balance, and recovery. By influencing glucose homeostasis, fat oxidation, and systemic inflammation, tirzepatide may enhance athletic performance. This review examines its pharmacological effects, impact on body composition, and implications for endurance, strength, and recovery in athletes, while addressing ethical and regulatory considerations, including anti-doping concerns.